Evaluation of Prescription and Non-Prescription Services in Pharmaceutical Facilities: A Patient Simulation Study in the Lamongan Region: Evaluasi Pelayanan Resep dan Non Resep di Fasilitas Kefarmasian: Studi Simulasi Pasien di Wilayah Lamongan - Cici Sayyidatul Adhimi; Primanitha Ria Utami; Enggar Ayu Fifianti; Erika Cindiana Pramudia Putri; Heru Setiawan; Lailya Eka; Muhammad Hadi Ma'ruf (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Pharmaceutical Services is an activity in identifying, preventing and resolving drug problems related to health. A new paradigm that is currently (patient oriented) with the aim of improving the quality of life of patients with an understanding of a drug or drug prescription from a doctor. This study aims to describe the implementation of prescription and non-prescription services based on Pharmaceutical Service Standards by pharmacists and pharmacists in the Lamongan area. This research is a descriptive research conducted by observation using patient simulation techniques. The location in the Lamongan area. The time of the study was November - December 2022. The sample consisted of 34 pharmacists who provide self-medication services at the Lamongan pharmaceutical facility, which were using the simple random sampling technique. The instruments used for data collection were scenarios of self-medication patients (for cases of fever, cough, runny nose), observation sheets, standard checklists for pharmaceutical services. The results of the study indicate that prescription and non-prescription services carried out by pharmacists in Lamongan have not fully complied with regulatory standards regarding pharmaceutical services. A total of 70.23% met pharmaceutical service standards. Special attention is needed in developing pharmaceutical competence, especially in providing effective patient education.